APLIKASI DRAWING REALISTIK MELALUI TEKNIK CUKIL DALAM KARYA SENI GRAFIS M. FADHLIL ABDI - Nurjanah, Devy Ika; Basuki, Rochmat (Institut Seni Indoensia Surakarta, 2022)
The relief print technique is one of the 4 types of printmaking techniques (the categorization is based on the process of its creation, namely the relief print technique, intaglio, flat printing, and silkscreen printing). The character of the engraver in high printing techniques tends to be firm, masculine, rigid and difficult to achieve plasticity. This is because the matrix/cliché material used is usually hard. In addition, the tapping tool used is in the form of iron / steel metal with a blade formed arch, so that the resulting carved lines are wider and larger, and it is more difficult to make curved lines, small, thin (as thin as a pencil or pen scratch). However, in the printmaking work of M. Fadhlil Abdi was able to achieve a realistic form using the woodcut technique. Fadhlil is a painting artist from Palembang who is active in art and exhibits both at home and abroad. Fadhlil's paintings are more of a realistic portrait. The purpose of this study is to examine the electrical technique of the works of printmaking of M. Fadhlil Abdi. How Fadhlil applies realistic drawing is usually applied by drawing/painting directly on the canvas, but here using printmaking techniques that are relatively more difficult to be able to achieve characters with subtle light dark gradations. The method used in this study is descriptive qualitative using the phenomenological theory approach.